Comparing Drone and Vessel‐Based Imaging to Quantify Epibiont Coverage on Humpback Whales - Isabel A. R. Taylor; Ticiana Fettermann; Barry McGovern; David S. Schoeman; Adrian B. McCallum; Stephanie H. Stack (Marine Mammal Science, 2026)
Cetacean epibionts offer noninvasive insights into host health, physiology, and spatial ecology, yet quantitative assessments in wild populations remain scarce. Although vessel‐based observations may be limited by field of view and analyst input, unoccupied aerial vehicles (UAVs; drones) are increasingly used to monitor cetacean health indices, enhancing observational availability and reproducibility. However, the suitability of drones for quantifying epibiota has not been thoroughly evaluated. Implementing a standardized workflow, we compared dorsal proportional epibiont coverage estimates derived from drone‐based imagery and traditional vessel‐based techniques across reproductive classes of humpback whales ( Megaptera novaeangliae ). We analyzed 32 paired datasets using pixel‐based methods, incorporating semiautomated graph‐cut segmentation and iterative color‐thresholding. Drone‐derived estimates of epibiont coverage consistently exceeded vessel‐based measures, which averaged 58% of the relative coverage estimated from corresponding drone imagery, partly attributable to variable lighting during image capture. Nevertheless, 94% of paired observations differed by less than 5% in absolute coverage, indicating strong agreement. While refinement of flight parameters, image resolution, and further validation are recommended, we demonstrate that drones can provide a reliable source of quantitative epibiont data, with potential applicability across diverse epibiont–host systems, benefiting cetacean population health monitoring programs and informing conservation strategies, particularly for elusive or understudied species.

Humpback Highs and Lows Amid Shifting Seas and a Northeast Pacific Marine Heatwave: Whale Demographics in the Main Hawaiian Islands, 2002–2023 - S. M. Barber‐Meyer; T. Cheeseman; J. Barlow; L. Bejder; A. L. Bradford; R. Cartwright; M. Deakos; L. Evans; R. Finn; C. M. Gabriele; B. Goodwin; C. Hayslip; et al. (Marine Mammal Science, 2026)
North Pacific humpback whales are a celebrated conservation success, rebounding from extensive commercial whaling. Yet they remain vulnerable to the impacts of climate change, a multifaceted stressor that can exacerbate existing threats. During 2013–2016, a Northeast Pacific marine heatwave severely reduced forage availability in their feeding grounds, concurrent with diminished whale recruitment and increased mortality. We analyzed photo‐identification data of whales that visited the Main Hawaiian Islands from 2002 to 2023 to estimate apparent survival, abundance, and distinct population segment (DPS) growth rates. Survival was high prior to (0.987; SE = 0.003), low during (0.684; SE = 0.022), and higher, but still reduced, after (0.956; SE = 0.006) the heatwave. Annual breeding season abundance estimates averaged 11,617 (SD = 1914) and included a striking 37% decrease from 2014/15 to 2021/22. While the average annual DPS growth rate was stable (1.00) over 20 breeding seasons, shorter periods included high growth (1.09) and steep decline (0.783). Depressed survival and abundance estimates may signal lingering heatwave effects or adjustment to current carrying capacity. Climate change predictions include more frequent, intense, and longer heatwaves; thus, this DPS serves as a crucial ecosystem‐health indicator. Continued research and monitoring are essential to support resiliency against future climate perturbations.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Use of physical examination, electrocardiography, radiography, and biomarkers to predict echocardiographic stage B2 myxomatous mitral valve disease in preclinical Cavalier King Charles Spaniels - S. Wesselowski; S.G. Gordon; R. Fries; A.B. Saunders; K.T. Sykes; J. Vitt; B. Boutet; J. Häggström; S. Kadotani; J. Stack; B.G. Barnett (Journal of Veterinary Cardiology, 2023)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Seasonal variation in nitrogenous components and bioactivity of protein hydrolysates from Porphyra dioica - Julianne Stack; Paul R. Tobin; Anna Gietl; Pádraigín A. Harnedy; Dagmar B. Stengel; Richard J. FitzGerald (Journal of Applied Phycology, 2017)

The effects of environmental factors on rainbow smelt Osmerus mordax embryos and larvae - K. M. Fuda; B. M. Smith; M. P. Lesser; B. J. Legare; H. R. Breig; R. B. Stack; D. L. Berlinsky (Journal of Fish Biology, 2007)
Experiments were conducted to identify environmental factors that influence the survival of rainbow smelt Osmerus mordax during their early life stages. Developing rainbow smelt embryos and yolk‐sac larvae were cultured under controlled conditions with different dissolved oxygen (DO; 1·09, 2·18, 4·37 and 6·55 mg l −1 , pH (4·0, 4·5, 5·0, 5·5, 6·0 and 7·0), nitrate ( 0·7, 3·6, 7·3, 14·6 and 29·2 mg l −1 ), phosphate (0·04, 0·21, 0·42, 2·08 and 4·17 mg l −1 ) and salinity (0, 5, 10, 15, 20 and 30) levels. Rainbow smelt embryos were also incubated with simulated tidal salinity fluctuations (2–28), ultraviolet radiation (irradiances of 2·8, 6·2 and 5·1 W m −2 ) and under natural conditions in two rainbow smelt spawning rivers. In the laboratory, hatch was only impaired under the lowest DO and pH conditions (0 and 13% hatch, respectively) and at highest constant salinity levels (0% hatch). Larval survival was only affected by pH levels ≤5·0. The experiment that compared hatch under natural conditions was terminated when embryos became covered with silt and fungus. These results suggest that water acidification, sediment and fungal growth may affect rainbow smelt survival during their early life stages.

DNA markers for Fusarium head blight resistance QTLs in two wheat populations - J. A. Anderson; R. W. Stack; S. Liu; B. L. Waldron; A. D. Fjeld; C. Coyne; B. Moreno-Sevilla; J. Mitchell Fetch; Q. J. Song; P. B. Cregan; R. C. Frohberg (Theoretical and Applied Genetics, 2001)